Health monitoring of light-weight structures - Lam, Wei Li (2016)
The Electromechanical Impedance (EMI) technique is a leading form of Structural Health Monitoring (SHM) method in the detection of structural damages, while the piezoelectric lead-zirconate-titanate (PZT) transducer serves as a medium in quantifying these damages, in terms of admittance signatures. When evaluating damage, lateral shifts in conductance peaks and root mean square deviation (RMSD) analysis are utilised to quantify the admittance signatures, and to compare between its healthy and deteriorated states. To narrow down damage intensity and position, nine PZTs and strain gauges are introduced to collect conductance signatures and strain data. For this study, loading effect is induced by means of incremental displacement and damage is induced by progressive hole sizes. In order to examine the extent of damage induced, the data is assessed and correlated with finite element analysis. The result from the attempted approach is unexpectedly poor, though this could have been attributed to either mishandling of sensors or improper experimental procedures.